The Presence of Physics Education Research in the Curriculum of an Initial Teacher Education Programme - Jesus, A. C.S.; Nardi, R. [UNESP] (IOP Publishing, 2019)
The objective of this study is to understand how a curriculum of an initial physics teacher education programme introduces elements of research in physics education for future teachers. This study is justified by the need to reduce the gap between what educational research outcomes says and what is practiced in the classroom, taking the initial teacher training as a possible way to bridge this gap. We present analysis of curricular documents of an initial teacher education programme in Brazil, mainly the Pedagogical Project and Teaching Plans of the subjects Methodology and Practice of Physics Teaching, and we based on Discourse Analysis as a theoretical-methodological framework. Analysis of the curricular documents of the programme indicates that there are several topics that are being studied by the researchers in physics education such as alternative conceptions, CTS relations and didactic laboratories, present in the curriculum. However, the various possible interpretations for teaching issues can provide different meanings between research outcomes, teacher training and physics teaching.